2002
DOI: 10.1016/s0926-6410(02)00138-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic patterns make the premotor cortex interested in objects: influence of stimulus and task revealed by fMRI

Abstract: Research in monkey and man indicates that the ventrolateral premotor cortex (PMv) underlies not only the preparation of manual movements, but also the perceptual representation of pragmatic object properties. However, visual stimuli without any pragmatic meaning were recently found to elicit selective PMv responses if they were subjected to a perceivable pattern of change. We used functional magnetic resonance imaging (fMRI) to investigate if perceptual representations in the PMv might apply not only to pragma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 65 publications
2
18
1
Order By: Relevance
“…Furthermore, a recent study by Schumacher and D'Esposito (2002) reported a dissociation of extrastriate visual areas and a fronto-parietal network related to stimulus encoding and response selection. The ventral premotor cortex has been shown to be involved in the sensory processing of objects (Schubotz & von Cramon, 2002). We assume that the premotor cortex activation reflects the pragmatic features of the attended cue (Schubotz & von Cramon, 2002;Fadiga, Fogassi, Gallese, & Rizzolatti, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study by Schumacher and D'Esposito (2002) reported a dissociation of extrastriate visual areas and a fronto-parietal network related to stimulus encoding and response selection. The ventral premotor cortex has been shown to be involved in the sensory processing of objects (Schubotz & von Cramon, 2002). We assume that the premotor cortex activation reflects the pragmatic features of the attended cue (Schubotz & von Cramon, 2002;Fadiga, Fogassi, Gallese, & Rizzolatti, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…3. Example for the serial prediction task paradigm (from Schubotz and von Cramon, 2002b, reproduced by permission of the publisher). A sequence of stimuli is presented either in the visual or in the auditory domain.…”
Section: Dorsal Versus Ventral Pmmentioning
confidence: 99%
“…For instance, PM activation is found when serial prediction is contrasted with an equally difficult serial match-to-sample task (Figs. 4C and 4D) (Schubotz and von Cramon, 2002b). The relevance of a predictive task for PM engagement may also be reflected by the absence of PM activation in a motion observation task that does not require prediction (Perani, 2001).…”
Section: (A) Pm Is Engaged In Prospective Attention To Sensory Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…- 56-al., 2009;Mazza et al, 2005;Stagg et al, 2004;Tales & Butler, 2006;Tales, Haworth, Wilkock, Newton, & Butler, 2008;Tales, Newton, Troscianko, & Butler, 1999) ,サ イズ(Kimura, Katayama, & Murohashi, Blakemore, Wolpert, & Frith, 2000;Brunia, 1999;Gomez, Vaquero, & Vaquero-Marrufo, 2004;Kveraga, Ghuman, et al, 2007; Schröger, & Schubotz, 2008;Schubotz, 2007;Schubotz & von Cramon, 2001a, 2001b, 2002a, 2002b, 2002cWolfensteller, Schubotz, & von Cramon, 2004 …”
mentioning
confidence: 99%